Monitoring and Varietal Screening Cucurbit Fruit Fly, Bactrocera cucurbitae Coquillett (Diptera: Tephritidae) on Cucumber in Bhaktapur and Kathmandu, Nepal - Maharjan, Ranju; Regmi, Rajendra; Poudel, Kapil (International Journal of Applied Sciences and Biotechnology, 2015)
Monitoring of cucurbit fruit fly by using four different types of traps was conducted in Sipadole VDC of Bhaktapur district during 2012 to observe the population dynamics. Three different types of fruit flies were recorded, in which the number of B. cucurbitae dominated to other species. Only B. cucurbitae damaged the cucumber, which was trapped 92.68%, 87.05%, 90.61%, and 69.38% in cue-lure, banana pulp bait, sticky traps and fly catcher, respectively. The highest number of fruit flies (167.5 male fruit flies/3traps) was recorded in cue-lure trap during the first week of September, which coincided with 85.45% RH and 21.67°C and 25.04°C minimum and maximum temperature, respectively. Positive relation of temperature, relative humidity and fruit fly catches was observed. Thus, cue-lure was the most effective traps for monitoring of fruit fly population. In varietal screening, among the six different varieties of cucumber, i.e. Kathmandu local, Kusle, Kamini, Malini, Kasinda and Mahyco Green Long, they were highly significant difference in yield. Kamini gave the highest marketable fruit 26.66 mt/ha yield and the lowest by Kusle (5.05 mt/ha). All the varieties were affected by cucurbit fruit fly. The highest number of unmarketable fruit set was observed in Kamini (22.29 fruits/plant). Int J Appl Sci Biotechnol, Vol 3(4): 714-720